Pemberdayaan Dukungan Psikologis Keluarga Dengan Kepatuhan Diet Pasien Diabetes Mellitus Di Desa Bontolempangan Kecamatan Bontoa - Faisal Asdar; Irmayani I; Alfiah A (Idea Pengabdian Masyarakat, 2022)
Seeing the increase in the incidence of diabetes mellitus globally, which is mostly caused by changes in unhealthy lifestyle patterns. One of the strategies to assist the management of patients with type 2 diabetes mellitus is to approach the closest person, namely the family, such as the problem of diet non-compliance caused by lack of family support. Therefore, high motivation is needed for family participation so that the community service team feels it is important to carry out community service through empowering family psychological support with dietary compliance of diabetes mellitus patients. This service is carried out in Bontolempangan Village, Bontoa District, Maros Regency. The method of service is by Lectures / counseling, discussions and questions and answers. As a result of the service, we got enthusiastic people who are active in asking questions so that there is an increase in intellectual function in patients and their families and is committed to providing support to their families who suffer from diabetes mellitus